2017
DOI: 10.1111/pbr.12505
|View full text |Cite
|
Sign up to set email alerts
|

Mapping quantitative trait loci associated with starch paste viscosity in rice (Oryza sativa L.) under different environmental conditions

Abstract: A recombinant inbred line (RIL) population consisting of 153 lines derived from a cross between indica ‘Zhongyouzao8’ and japonica ‘Toyonishiki’ rice was used to detect stable quantitative trait loci (QTL) for rapid visco analyser (RVA) characteristics under four environmental conditions. We identified 93 QTL for RVA profiles, and four pleiotropic regions harbouring stably expressed QTL were detected on chromosomes 2, 6, 7 and 11. These newly identified and stable QTL will facilitate further research into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 51 publications
(83 reference statements)
4
16
0
Order By: Relevance
“…Other loci for RVA parameters associated with SSR markers were detected in individual subpopulation and only in 1 year, which distributed on Chr.1, 4, 7, 8, 9 and 10. The accuracy of these loci needs to be verified in future, even though most of them have been identified in natural or linkage populations based on different genetic background [ 15 , 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other loci for RVA parameters associated with SSR markers were detected in individual subpopulation and only in 1 year, which distributed on Chr.1, 4, 7, 8, 9 and 10. The accuracy of these loci needs to be verified in future, even though most of them have been identified in natural or linkage populations based on different genetic background [ 15 , 37 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…These traits were not measured in the RIL population in this current study; however, the results revealed among the 106 diverse varieties signal existing associations between TPA traits and AAC (Table 4.2). Despite these presence of large-effect QTLs and results corroborating with previous studies (Bao et al, 2000, Yao et al, 2017, the drawback in this current QTL mapping effort is the absence of environmental factor;…”
Section: Qtls For Aac and Rva Traits In The Populationsupporting
confidence: 86%
“…More than 200 starch RVA trait QTLs were localized using various mapping populations [3,6,[17][18][19][20][21][22][23]. A few QTLs have been cloned or subjected to ne-mapping (http://www.gramene.org/, http://www.ricedata.cn/).…”
Section: Introductionmentioning
confidence: 99%
“…Certain varieties with the same allele of Wx have different ECQs, implying that any other QTLs effect on ECQs. Because the effects of minor QTLs might be covered by major QTL such as Wx, many populations derived from bi-parental with similar AC values or the same Wx background have been developed to detect QTLs for starch RVA and eliminate the Wx effects [21,22,24,25]. The heredity of starch RVA pro le characters is very complex and affected by environmental factors [17,26].…”
Section: Introductionmentioning
confidence: 99%